KAJIAN KONSEPTUAL PERILAKU PROSOSIAL DALAM PERSPEKTIF PSIKOLOGI SOSIAL - Islamy, M. Irfan (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
Human are homo economicus creatures who always trying to maximize their satisfaction by acting rationally, but they have a desire to see the happiness of others, its called prosocial behavior. Prosocial behavior intended to benefit another", is a social behavior that benefits other people or society as a wholesuch as helping, sharing, donating, andÂ  volunteering, human beings as homoeconomicus beings also known as homo socius.Keywords: Prosocial, Behavior